New opportunities for lowering low-density lipoprotein cholesterol: comparative characteristics of PCSK9-targeted therapy - S. K. Zyryanov; O. I. Butranova (Российский кардиологический журнал, 2022)
The spread of cardiovascular diseases has the nature of an epidemic, which is enhanced by lipid profile disorders, manifested by hypercholesterolemia. Numerous conventional pharmacological tools for lowering cholesterol associated with low density lipoproteins do not make it possible to achieve target values in various categories of patients. Inhibition of proprotein convertase subtilisin/ kexin type 9 (PCSK9) is a promising target in the management of patients with atherosclerotic diseases and includes two main tools — monoclonal antibodies (Alirocumab and Evolocumab) and a small interfering RNA drug (Inclisiran). The presented review is devoted to a comparative analysis of the efficacy and safety of drugs from these groups.